2003
DOI: 10.1002/pros.10301
|View full text |Cite
|
Sign up to set email alerts
|

Results of a genome‐wide linkage analysis in prostate cancer families ascertained through the ACTANE consortium

Abstract: Genetic susceptibility to prostate cancer is likely to be controlled by many loci, with no single gene explaining a large fraction of the familial risk. Pooling of results from all available genome scans is likely to be required to obtain definitive linkage results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…We hypothesized that SNPs may influence the generation of ERG fusion, which is an early event in CaP carcinogenesis. A genome-wide linkage analysis found that several loci located on chromosomes 9, 18, and X are associated with the development of fusion-positive prostate cancer; however, these studies were performed in familial prostate cancer [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that SNPs may influence the generation of ERG fusion, which is an early event in CaP carcinogenesis. A genome-wide linkage analysis found that several loci located on chromosomes 9, 18, and X are associated with the development of fusion-positive prostate cancer; however, these studies were performed in familial prostate cancer [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…We collected all germline BRCA variants reported in these studies. Some of these studies did not specify if these variants are variants of unknown significance (VUS) or pathogenetic [22,25,28,37,[39][40][41]46], as they reported only the overall number of identified mutations; other studies [31,34,38] included both VUS and pathogenetic germline BRCA variants. To provide additional information for further studies, when variants' nomenclature was available in the original study, we have revised these alterations in accord with the most recent ClinVar classification.…”
Section: Limitationsmentioning
confidence: 99%
“…Thus far, several GWS have been reported for prostate cancer [ 1 , 3 , 5 , 57 - 72 ]. The significant results are summarised as follows:…”
Section: Genome Searches In Prostate Cancermentioning
confidence: 99%
“…7q, 19q [ 89 - 91 ]. Eight GWS have been published recently in one issue of the Prostate (ACTANE Consortium [ 72 ]; Lange et al [ 65 ]; Schleutker et al [ 66 ]; Cunningham et al [ 67 ]; Xu et al [ 68 ]; Wiklund et al [ 69 ]; Janer et al [ 70 ]; Witte et al [ 71 ], Dec 2003). A summary of these was published in an accompanying review by Easton (2003) [ 5 ].…”
Section: Genome Searches In Prostate Cancermentioning
confidence: 99%